2014
DOI: 10.1007/978-94-017-9153-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αEβ7: Molecular Features and Functional Significance in the Immune System

Abstract: Alpha E beta 7 (αEβ7) is an α-I domain-containing integrin that is highly expressed by a variety of leukocyte populations at mucosal sites including intraepithelial T cells, dendritic cells, mast cells, and T regulatory cells (Treg). Expression depends largely or solely on transforming growth factor beta (TGF-β) isoforms. The best characterized ligand for αEβ7 is E-cadherin on epithelial cells, though there is evidence of a second ligand in the human system. An exposed acidic residue on the distal aspect of E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 115 publications
1
29
0
2
Order By: Relevance
“…The expression of CD69 and CD103, two proteins thought to enhance retention of T cells in tissue (16, 17), was compared on total CD4+ and CD8+ T cells isolated from PBMC and cervical samples. Representative data (Figure 2A) and summarized data (Figure 2B) show that CD69 was expressed on a higher proportion of CD4+ (medians 81.1% versus 0.8%, P=0.008) and CD8+ T cells (medians 75.7% versus 3.2%, P=0.008) isolated from cervical biopsies versus blood (n=9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CD69 and CD103, two proteins thought to enhance retention of T cells in tissue (16, 17), was compared on total CD4+ and CD8+ T cells isolated from PBMC and cervical samples. Representative data (Figure 2A) and summarized data (Figure 2B) show that CD69 was expressed on a higher proportion of CD4+ (medians 81.1% versus 0.8%, P=0.008) and CD8+ T cells (medians 75.7% versus 3.2%, P=0.008) isolated from cervical biopsies versus blood (n=9).…”
Section: Resultsmentioning
confidence: 99%
“…Surface expression of CD69, an early leukocyte cell activation marker, has been shown to interfere with sphingosine-1-phosphate receptor function leading to T cell retention and local memory formation (16). CD103, a constituent of αEβ7 integrin, participates in T cell retention through interaction with E-cadherin expressed on epithelial cells (17). Studies of human organ donors revealed that the highest frequency of CD69 expression was on tissue-derived CD4+ and CD8+ T RM , and that CD103 was most highly expressed by gut-derived CD8+ T cells (21, 25).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, ltgb7−/ − mice also lacks CD103. However, CD103 mainly plays a role for the retention of T cells in the epithelia whereas α4β7 is responsible for trafficking (39). Our results with ltgb7−/ − mice show that the enhanced local E7-specific CD8+ T cell response by our vaccination approach is mainly mediated by α4β7 (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…It is a known ligand of E-cadherin, a homotypic adhesion molecule expressed by epithelial cells in barrier tissues 58 . In mouse models, CD8 T cells specific for HSV-1 enter the skin lacking CD103 expression, and then in response to epidermal TGFβ upregulate CD103 6 .…”
Section: Common Features Of Trm In Barrier Tissuesmentioning
confidence: 99%